Finite Element Analysis and Parametric Study of Panel Zones in H-Shaped Steel Beam–Column Joints - Wei Li; Hai-Tao Fan; Heng Ye; Xu-Chuan Lin; Lian-Meng Chen (Buildings, 2023)
This paper investigates the mechanical properties of a traditional welded rigid joint with a weakened panel zone under seismic load. The created finite element model is calibrated by the high-strength steel joint test, carried out by the team in the early stage, and the effectiveness of the finite element method was verified. The finite element software ABAQUS is used to investigate the influence of different joint web thicknesses on the mechanical properties of middle column joints under a low-cyclic-loading test. Supported by a validated numerical model, the ductility, energy dissipation, and other properties of different thicknesses of panel zone column webs are carefully analyzed. The results indicate that the thickness of the web plate in the panel zone significantly affects the location of the joint plastic hinge. The ultimate loading capacity of the joints increased significantly with an increase in the thickness of the webs in the panel zones. Compared with the joint with a weakened panel zone, the hysteresis curve of the strengthened joint is fuller; meanwhile, it cannot alleviate the stress concentration at the weld holes of the web. When the thickness of the joint domain web is too weak, excessive deformation in the joint domain will lead to a decrease in the bearing capacity of the joint, causing damage. The stiffness degradation coefficient of the web-thickened specimen was found to be dominated and controlled by the stiffness of the beam; however, with an increase in the thickness of the web, the stiffness degradation coefficient remained basically unchanged. Finally, a recommendation for weakened beam–column interior joints based on the steel frame panel zone is made, which will lay a foundation for the simulation and analysis of the seismic performance of this structure.